2017
DOI: 10.1037/aca0000112
|View full text |Cite
|
Sign up to set email alerts
|

Music education, academic achievement, and executive functions.

Abstract: This study examined whether music education was associated with improved performance on measures of academic achievement and executive functions. Participants were 265 school-age children (Grades 1 through 8, 58% female, and 86% African American) who were selected by lottery to participate in an out-of-school program offering individual- and large-ensemble training on orchestral instruments. Measures of academic achievement (standardized test scores and grades in English language arts and math) were taken from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
105
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 97 publications
(182 reference statements)
22
105
1
4
Order By: Relevance
“…Moreno and colleagues quasi-randomly assigned children to receive computerized music training or visual arts training and found that the musical-training group showed better behavioral performance as well as a greater index of brain plasticity on no-go trials in a go/no-go task (Moreno et al, 2011;see Moreno & Farzan, 2015, for discussion). Similarly, children who enrolled in after-school music lessons also showed improvement on multiple tasks of inhibitory control (go/no-go, Stroop, and flanker tasks), as compared to a waitlist (no-contact) control group (Holochwost et al, 2017). In contrast, Bugos and DeMarie (2017) found more equivocal results, in which preschool children assigned to music lessons outperformed children assigned to Lego-building lessons on one test of inhibitory control (a matching-familiar-figures test), but not on another (a day/night Stroop task).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Moreno and colleagues quasi-randomly assigned children to receive computerized music training or visual arts training and found that the musical-training group showed better behavioral performance as well as a greater index of brain plasticity on no-go trials in a go/no-go task (Moreno et al, 2011;see Moreno & Farzan, 2015, for discussion). Similarly, children who enrolled in after-school music lessons also showed improvement on multiple tasks of inhibitory control (go/no-go, Stroop, and flanker tasks), as compared to a waitlist (no-contact) control group (Holochwost et al, 2017). In contrast, Bugos and DeMarie (2017) found more equivocal results, in which preschool children assigned to music lessons outperformed children assigned to Lego-building lessons on one test of inhibitory control (a matching-familiar-figures test), but not on another (a day/night Stroop task).…”
mentioning
confidence: 93%
“…The relationships between musical ability and EFs have mostly been demonstrated in correlational studies, and these links could reflect a few possibilities. One possibility is that musical experience draws strongly on some (or all) aspects of EFs, which leads to collateral benefits, or transfer effects, to those EF abilities more broadly (e.g., Holochwost et al, 2017). This might mean that musical training could serve to improve EFs more broadly (i.e., as a type of relatively enjoyable cognitive training).…”
mentioning
confidence: 99%
“…Studies assessing executive functions before and after a period of music-based interventions have shown that music training is associated with enhancements in working memory [ 28 , 29 ], performance on an inhibition task [ 30 ], and on a test of attentional control [ 29 ]. A recent longitudinal study with children found that random assignment in an after-school music training program was associated with enhanced performance on several tasks of cognitive control and response inhibition [ 31 ]. However, an effect of music-based interventions on measures of executive function was not replicated in another large-scale study of children between the ages of 6–14 [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, children who enrolled in after-school music lessons also showed improvement on multiple tasks of inhibitory control (go/no-go, Stroop, and flanker tasks) compared to a waitlist (no contact) control group (Holochwost et al, 2017). In contrast, Bugos and DeMarie (2017) found more equivocal results, where preschool children assigned to music lessons outperformed children assigned to Lego-building lessons on one test of inhibitory control (a matching familiar figures test), but not on another (a day/night Stroop task).…”
Section: Introductionmentioning
confidence: 93%